The Development of a Collaborative Binational Strategy to Support the San Diego-Tijuana Transborder Community During the COVID-19 Pandemic - Barbara Jiménez; Barbara Jiménez; Barbara Jiménez; Justine Kozo; Justine Kozo; Justine Kozo (Frontiers Media S.A., 2022)
The COVID-19 pandemic illustrates the need for and importance of cross-border public health collaboration. San Diego, California and Tijuana, Baja California are an interconnected region with one of the busiest international borders in the world and hundreds of thousands bi-directional crossings each day. As the sister cities witnessed the rising case numbers early in the pandemic, it became essential and urgent to implement a formal structure to facilitate cross-border COVID-19 communication, coordination, and collaboration. The present article describes how the development of a Collaborative Binational Strategy led to coordinated outreach and initiatives that addressed access and equity in the transborder region. Through examples, the article illustrates how regional leaders in San Diego and Tijuana harnessed existing transborder partnerships to collaboratively build infrastructure and communication pathways to exchange data, guidance, troubleshoot shared challenges, build capacity, and establish cross-border testing and vaccine opportunities. The challenges, lessons learned, and best practices may inform other multi-level, interdisciplinary, and cross-border jurisdictions on how to support a transborder community during a pandemic or other health emergency.